2020
DOI: 10.1212/wnl.0000000000009700
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 presenting with ophthalmoparesis from cranial nerve palsy

Abstract: A 36-year-old man with a history of infantile strabismus presented with left ptosis, diplopia and bilateral distal leg paresthesias. He reported subjective fever, cough and myalgias which had developed 4 days earlier and resolved before presentation. Exam was notable for left mydriasis, mild ptosis and limited depression and adduction, consistent with a partial left oculomotor palsy. Abduction was limited bilaterally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
265
3
32

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(307 citation statements)
references
References 7 publications
7
265
3
32
Order By: Relevance
“…The ophthalmological involvement during the coronavirus infection occurs in the 12 days later [ 13 ]. Another paper reported 2 cases of ophthalmoplegia associated with neurological impairment [ 14 ], but improvement in both of these patients was slower than in our case. Our patient presented a painless left ophthalmoplegia with binocular diplopia and without headache or other signs of central nervous system involvement.…”
Section: Discussioncontrasting
confidence: 74%
“…The ophthalmological involvement during the coronavirus infection occurs in the 12 days later [ 13 ]. Another paper reported 2 cases of ophthalmoplegia associated with neurological impairment [ 14 ], but improvement in both of these patients was slower than in our case. Our patient presented a painless left ophthalmoplegia with binocular diplopia and without headache or other signs of central nervous system involvement.…”
Section: Discussioncontrasting
confidence: 74%
“…Across three recent studies, one patient presented with partial third nerve palsy and accompanying bilateral sixth nerve palsy, one with complete third nerve palsy only, one with bilateral sixth nerve palsy, and two with unilateral sixth nerve palsy. , 7,8,9 Similar to the two aforementioned cases, the precise mechanism in our case remains unknown. In these previously mentioned studies, patients who presented with third nerve palsy with or without additional sixth nerve palsy demonstrated a more severe manifestation of their infection and required more intensive, in-patient treatment.…”
Section: Discussionmentioning
confidence: 57%
“…GBS occurred in 5/1200 (0.4%) patients with COVID-19 in one of the studies [13]. There were six other case report of GBS, one Miller Fisher syndrome, and two polyneuritis cranialis [14,[24][25][26][27][28][29][30]. Interestingly, neurotropism of human coronaviruses has been suggested by in vitro and in vivo studies that showed that certain strains of the viruses could persist in the human CNS by targeting oligodendrocytic and neuroglial cell lines [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one patients experienced a cerebrovascular complication, with 27 ischemic strokes [11,[19][20][21][22][23], 3 hemorrhagic strokes [11,15,23] and 1 cerebral venous sinus thrombosis [11]. There were 15 patients with GBS [13,14,[24][25][26][27][28][29][30] or its variants, 6 reported as encephalitis [12,18,[31][32][33], one with seizures [34], one with acute hemorrhagic necrotizing encephalopathy [16] one reported as transverse myelitis [35], and one reported as ADEM [36]. Nine of these cases were reported as fatal.…”
mentioning
confidence: 99%